Protein Nanotechnology Protocols, Instrumentation, and Applications, Second Edition - Gerrard, Juliet A.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2013)
Since the first edition of Protein Nanotechnology Protocols Instruments and Applications the intersection of protein science and nanotechnology has become an exciting frontier in interdisciplinary sciences. The second edition of Protein Nanotechnology Protocols Instruments and Applications expands upon the previous editions with current, detailed chapters that provide examples of proteins which are now being harnessed for a wide range of applications, some more developed than others. This book also delves into engineering proteins and an overview of the sorts of tools that are now readily available to manipulate the structure and function of proteins, both rationally and using methods inspired by evolution. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Authoritative and practical, Protein Nanotechnology Protocols Instruments and Applications, Second Edition seeks to provide an overview of this multi-faceted field and a useful guide to those who wish to contribute to it.
Protein Nanotechnology – What is it? -- Bioengineered Silk Proteins to Control Cell and Tissue Functions -- Aqueous-based Spinning of Fibers from Self-Assembling Structural Proteins -- Fibrous Protein Nanofibres -- Self-assembling Nanomaterials: Monitoring the Formation of Amyloid Fibrils, with a Focus on Small Angle X-ray Scattering -- Amyloid Fibrils from Readily Available Sources: Milk Casein and Lens Crystallin Proteins -- Formation of Amphipathic Amyloid Monolayers from Fungal Hydrophobin Proteins -- Proteins and Peptides as Biological Nanowires: Towards Biosensing Devices -- Nanotechnology with S-Layer Proteins -- Stimuli-responsive Peptide Nanostructures at the Fluid-fluid Interface -- Designed Self-assembling Peptides as Templates for the Synthesis of Metal Nanoparticles -- Purification of Molecular Machines and Nanomotors using Phage-derived Monoclonal Antibody Fragments -- Determination of Enzyme Thermal Parameters for Rational Enzyme Engineering and Environmental/Evolutionary Studies -- Rational-Based Protein Engineering: Tips and Tools -- Construction and Analysis of Randomized Protein-encoding Libraries using Error-prone PCR -- Droplets as Reaction Compartments for Protein Nanotechnology -- Label-Free, Real-Time Interaction and Adsorption Analysis 1: Surface Plasmon Resonance -- Label-Free, Real-Time Interaction and Adsorption Analysis 2: Quartz Crystal Microbalance -- Atomic Force Microscopy for Protein Nanotechnology.Atomic Force Microscopy for Protein Nanotechnology.
Keywords: Proteins .; Nanotechnology; Protein Science; Nanotechnology